Encyclopedia of Life Sciences 2011
DOI: 10.1002/9780470015902.a0023202
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular Junction

Abstract: The neuromuscular junction (NMJ) is the site of communication between motor nerve axons and muscle fibres. It is composed of four specialised cell types: motor neurons, Schwann cells, muscle fibres and the recently discovered kranocytes. The function of the NMJ is to transmit signals from the motor neuron to the skeletal muscle fibre quickly and reliably, to ensure precise control of skeletal muscle contraction and therefore voluntary movement. The reliability of transmission is aided by specialised architectu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Furthermore, it has also been demonstrated that denervated myotubes within a nerve-muscle co-culture system fail to exhibit contractile function or characteristics of mature development; they eventually deteriorate, despite the elevated concentration of nerve-derived secretions in the culture environment [ 50 ]. Interestingly, the myotubes in our co-culture model initiated spontaneous contractions as early as 72 h post co-culture [ 27 ], suggesting the initial emergence of NMJ formation, due to the myotube requirement for nervous input from the motor neurons to induce contraction [ 51 ]. When compared to aneural in vitro SkMC cultures, the benefits of our co-culture system are apparent, as co-cultured myotubes exhibit advanced stages of differentiation that monocultures of SkMCs fail to achieve.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has also been demonstrated that denervated myotubes within a nerve-muscle co-culture system fail to exhibit contractile function or characteristics of mature development; they eventually deteriorate, despite the elevated concentration of nerve-derived secretions in the culture environment [ 50 ]. Interestingly, the myotubes in our co-culture model initiated spontaneous contractions as early as 72 h post co-culture [ 27 ], suggesting the initial emergence of NMJ formation, due to the myotube requirement for nervous input from the motor neurons to induce contraction [ 51 ]. When compared to aneural in vitro SkMC cultures, the benefits of our co-culture system are apparent, as co-cultured myotubes exhibit advanced stages of differentiation that monocultures of SkMCs fail to achieve.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent binding of ACh by postsynaptic acetylcholine receptors (AChRs) in the plasma membrane of the muscle cell triggers muscle contraction. The ease of accessibility and comparative simplicity of the somatic NMJ have placed it at the forefront of discoveries about chemical synaptic transmission for over a century (Hong & Etherington, ).…”
Section: Introductionmentioning
confidence: 99%